ICAPRDT : proceedings - International Conference on Advances in Pattern Recognition and Digital Techniques( 3rd : 1993 : Calcutta ); International Conference on Advances in Pattern Recognition and Digital Techniques 3rd Calcutta, 1993 (Calcutta I S I, 1994)
This conference is a homage to memory of Late P C Mahalanobis, the founder of the Institute and the father of statistics in India in his birth centenary. The core programme of this conference is on Artificial Intelligence, Pattern Recognition, Speech, Vision and Image Processing and in Digital Techniques.
P C Mahalanobis Birth Centenary Volume
Keywords: Computer science; Pattern recognition